Inactivation of catalytic and non-catalytic PI3 kinase gamma functions enhances hypoxia-induced pulmonary hypertension in mice. (3rd October 2022) - Gnatzy-Feik, L; Berghausen, E; Vantler, M; Mueller, R; Zierden, M; Ghigo, A; Hirsch, E; Baldus, S; Rosenkranz, S
Abstract: Rationale: Pulmonary hypertension (PH) is a pulmonary vascular disease characterised by chronically elevated pulmonary arterial mean pressure, increased pulmonary vascular resistance and right ventricular (RV) dysfunction and hypertrophy. The pathogenesis includes vasoconstriction of pulmonary vessels and pulmonary vascular remodelling. Phosphatidylinositol 3'-kinase γ (PI3Kγ) is highly expressed in leukocytes, endothelial cells (EC) and cardiomyocytes, which are involved in the pathogenesis of PH. The catalytic function of PI3Kγ has been shown to be associated with numerous processes that are potentially important for both vascular remodelling and maladaptive cardiac hypertrophy, including leukocyte recruitment and endothelial cell proliferation and survival. However, inhibition of non-catalytic PI3Kγ function results in reduced nitric oxide (NO) production by endothelial NO synthase (eNOS), which may lead to increased vascular resistance. Therefore, the aim of our study was to investigate the role of both catalytic and non-catalytic PI3Kγ functions in the pathogenesis of PH. Methods: The importance of PI3Kγ in the pathogenesis of PH was analysed in vivo using the hypoxia-induced mouse model of PH (21 days at 10% O2 hypoxia (HOX)). PI3Kγ knockout mice (PI3Kγ−/−), as well as mice expressing a catalytically inactive form of PI3Kγ (PI3KγKD/KD) were investigated. To specifically inhibit the non-catalytic function of PI3Kγ, C57BL/6N mice were treated with a blocking peptide via intratracheal instillation and studied in the same model. Subsequently, systolic right ventricular pressure (RVSP) was measured using a Millar pressure catheter inserted via the jugular vein. In vitro, western blotting was used to investigate the phosphorylation of eNOS (Ser1177) in pulmonary ECs from wild type (WT), PI3Kγ−/− and PI3KγKD/KD mice. Results: PI3Kγ−/− mice showed significantly increased RVSP after three weeks of hypoxia compared with WT controls (HOX WT 34.16±3.47mmHg vs. HOX PI3Kγ−/− 37.04±2.43mmHg; p=0.005; n≥7). A significant increase in RVSP was also detected in PI3KγKD/KD and blocking peptide-treated mice (HOX WT 34.67±2.02mmHg vs. HOX PI3KγKD/KD 37.95±1.39mmHg; p=0.023; n≥5 and HOX vehicle 34.19±2.74mmHg vs. HOX blocking peptide 37.61±2.46mmHg; p=0.011; n≥9). Heart rate, as well as systemic blood pressure, remained unchanged. Under normoxic conditions, no difference in RVSP between the groups could be measured. Interestingly, western blot detected reduced phosphorylation of eNOS after stimulation with fetal calf serum in PI3Kγ−/− ECs compared to WT and PI3KγKD/KD. Conclusion: These results show that blunting of both catalytic and non-catalytic functions of PI3Kγ in vivo do not prevent the pathogenesis of PH, but conversely enhance hypoxia-induced elevation of RVSP. In this context, reduced phosphorylation of eNOS may play a crucial role, leading to increased vasoconstriction. Additional studies are required to evaluate the underlying mechanisms in detail. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): DFG Deutsche Forschungsgemeinschaft